Rapid diagnosis of rabies and post-vaccinal encephalitides - M. J. Warrell (2018)
In an attempt to establish the diagnoses of rabies post-vaccinal encephalitis (PVE) and early rabies encephalitis, paired serum and CSF levels of rabies neutralizing antibody (Rab) and rabies specific-IgM (RIgM) were compared in 12 PVE, 10 rabies and five control patients with similar presenting clinical features. Rapid methods of rabies antigen detection were evaluated in 17 patients. All 12 PVE patients had Rab in their serum and in eight it was also present in the CSF. These same eight had RIgM in the serum, and in seven also in the CSF. The CSF antibodies may have originated in the plasma since six patients had a high albumin quotient indicating leakage across the blood-brain barrier. Among the rabies patients, only the two vaccinated ones had serum Rab; this was also detected in the CSF of one and RIgM was in the CSF of the other. A raised IgG Index, indicating intrathecal synthesis of IgG was seen in five of 12 PVE patients. This did not correlate with the presence of CSF rabies antibody, suggesting production of antibody to other vaccine antigens of neural origin. The diagnosis of rabies encephalitis in life was made by antigen detection in a skin biopsy. No false positive results occurred and the method was as efficient as immunofluorescence of a post-mortem brain biopsy.